GOOGLE CLASSROOM AS LEARNING PLATFORM IN TEACHING WRITING - Ahmad Syafi'i (British : Jurnal Bahasa dan Sastra Inggris, 2020)
Technology today has played a major role in the field of education especially with the adaptation of World-Wide Web and fast internet networking such as 4G and 5G. Since traditional teaching activity is seen not more enough to support the students’ learning of English especially in the EFL context where the English are commonly used at school, university, or college educators have combined face to face interaction with an online course in blended learning. The Google Classroom is a networks platform for interaction among teachers and students, collaborate, share and evaluate homework, grades, class discussions, notices, and evaluations. Its objective is to help educators use social media power to customize the classroom for all students. Awareness of the positive potentials of this learning style will allow Google Classroom to introduce a mixed learning approach in the classroom. The post would discuss how Google Classroom facilitates English classroom teaching and learning writing. The argument continues with Google Classroom presentation and the idea of mixed education using Google Classroom. Then it continues with the application of this platform into actual teaching writing context and its outcome. Furthermore, the researchers will also discuss the current and future challenges of Google Classroom in ELT writing for EFL learners as well as teachers